Sarcopenia as a problem of old age - a form of rehabilitation - Szmelcer, Beniamin; Lamtych, Martyna; Zwolinski, Adrian; Lipka, Marta; Modlińska, Aleksandra; Kubiak, Karolina; Kontowicz, Marlena; Kwiatkowska, Klaudia; Krakowska, Natalia; Kuźba, Karolina; et al. (Journal of Education, Health and Sport, 2019)
Background: Sarkopenia as a disease has relatively recently become the object of research and the work of the academic community. Despite this, sarcopenia is an increasingly serious social problem, it can be seen in a large number of statistics and epidemiological studies. Among geriatric patients, along with their multiformity and the associated use of a large amount of medicines, it causes many negative effects related to the functioning of the whole organism as well as the quality of life of the patient himself. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: sarcopenia, geriatrics, rehabilitation, loss of muscle mass. Results: Among the studies and recommendations concerning sarcopenia, a continuous lack of clear, transparent and confirmed diagnostic criteria can be stated. At the diagnosis of this disease, an X-ray or a bioelectrical impedance analysis is used. Other methods used are functional tests, including a six-minute walk test or "Timed-Up and Go" test (TUG). In the case of rehabilitation of people with sarcopenia, the most effective form of kinesitherapy is individually selected resistive training, which has a positive effect not only on muscle mass growth, but also the body’s protein metabolism and the improvement of the endocrine system. Physiotherapy is the most commonly used method of physical therapy, among other methods of rehabilitation there are also therapeutic massage, aqua aerobics, vibratory training, and Nordic Walking and diet supplementation. Conclusions: Sarcopenia in geriatric patients, especially with ineffective treatment and rehabilitation, has a destructive impact on both the physical and mental sphere of the patient. There is a great need for more extensive research, both on the whole disease process and the effectiveness of forms of assistance to patients.